2006
DOI: 10.1103/physreva.73.025801
|View full text |Cite
|
Sign up to set email alerts
|

Atom localization via interference of dark resonances

Abstract: A scheme of atom localization based on the interference of resonance of double-dark states is proposed, in which the atom interacts with a classical standing-wave field. It is found that the localization property is significantly improved due to the interaction of double-dark resonances. It is realized that the atom is localized just at the nodes of the standing-wave field with higher precision. Moreover, an improvement by a factor of 2 in the detecting probability of a single atom within the subwavelength dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
72
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(72 citation statements)
references
References 22 publications
0
72
0
Order By: Relevance
“…This is because the resonance fluorescence spectrum exhibits a uniform position distribution and provide no information about the atom localization when the driving field is resonant with the atomic transition in the two-level system. Likewise, several authors showed that the Raman resonances become useless when the absorption spectra are employed in the schemes based on electromagnetically induced transparency [15,20]. In sharp contrast, for the present scheme, it is the resonance conditions that are most suitable for the atom localization.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…This is because the resonance fluorescence spectrum exhibits a uniform position distribution and provide no information about the atom localization when the driving field is resonant with the atomic transition in the two-level system. Likewise, several authors showed that the Raman resonances become useless when the absorption spectra are employed in the schemes based on electromagnetically induced transparency [15,20]. In sharp contrast, for the present scheme, it is the resonance conditions that are most suitable for the atom localization.…”
mentioning
confidence: 74%
“…At the same time, there is 50% detecting probability (an improvement by a factor of 2) of the atom within the subwavelength domain. The improvement is also achieved by employing the interference of double dark resonances [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zubairy and coworkers have discussed atom localization using resonance fluorescence and phase and amplitude control of the absorption spectrum [14][15][16], and Agarwal and Kapale presented a scheme [17] based on coherent population trapping (CPT). Also, one-dimensional (1D) atom localization can be realized via dual measurement of the field and the atomic internal state [18], double-dark resonance effects [19], phase and amplitude control of the driving field [20,21], coherent manipulation of the Raman gain process [22], or spontaneous emission [23,24]. Recently, atom localization has been demonstrated in a proof-of-principle experiment using the technique of electromagnetically induced transparency (EIT) [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several simple localization schemes have been proposed using such as the resonance fluorescence in a two-level system, the measurement of Autler-Townes split spontaneous emission in a three-level system, and a three-level -type atom interacting with a classical standing-wave field and a weak probe field [4][5][6]. Furthermore, one-dimensional (1D) atom localization can be achieved in Raman gain atoms [7], and coherent population trapping [8][9][10]. There will be more practical application in two-dimensional (2D) atom localization [11,12], and hence many works have been put forward.…”
Section: Introductionmentioning
confidence: 99%